2001
DOI: 10.1073/pnas.141366998
|View full text |Cite
|
Sign up to set email alerts
|

The human salivary peptide histatin 5 exerts its antifungal activity through the formation of reactive oxygen species

Abstract: Previous studies have shown that the human salivary antifungal peptide histatin 5 is taken up by Candida albicans cells and associates intracellularly with mitochondria. The purpose of the present study was to investigate the biological consequence of this specific subcellular targeting. Histatin 5 inhibited respiration of isolated C. albicans mitochondria as well as the respiration of intact blastoconidia in a dose and time-dependent manner. A nearly perfect correlation was observed between histatin-induced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
160
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(176 citation statements)
references
References 31 publications
13
160
0
3
Order By: Relevance
“…Our data regarding the respiratory activity of histatin-treated isolated mammalian mitochondria are in agreement with previous studies that reported a dosedependent inhibition of the respiratory activity and a large dissipation of the mitochondrial membrane potential (DW) in C. albicans cells, following histatin 5 exposure [17,19]. First, Helmerhorst et al suggested that histatin-5, after its entrance in the yeast cell, reaches the mitochondria and inhibits the complexes I and/or III of the respiratory chain.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our data regarding the respiratory activity of histatin-treated isolated mammalian mitochondria are in agreement with previous studies that reported a dosedependent inhibition of the respiratory activity and a large dissipation of the mitochondrial membrane potential (DW) in C. albicans cells, following histatin 5 exposure [17,19]. First, Helmerhorst et al suggested that histatin-5, after its entrance in the yeast cell, reaches the mitochondria and inhibits the complexes I and/or III of the respiratory chain.…”
Section: Discussionsupporting
confidence: 92%
“…It is interesting to note that the peptide at a concentration of 100 lM inhibits mitochondrial respiration only in the presence of glutamate-malate as substrates, implying that inhibition of respiration was occurring probably at the level of the complex I of the respiratory chain. It should be noted that, although the concentration of histatin-5 used in these experiments would not be achievable under physiological conditions, in earlier in vitro studies concerning the toxic effects of histatin-5 on cells, this peptide was used in similar concentration [11,17,19,22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Так, в работе [84] было высказано предположение, что токсичность антимикробного пептида хистатина-5 в отношении C. albicans, C. neoformans и некоторых других грибков обусловлена образованием активных форм кислорода (АФК) в их клетках под действием этого пептида. Авторы [84] выдвинули гипотезу о том, что после попадания в клетки микроскопических грибов хистатин-5 проникает в митохондрии и ингибирует цикл кофермента Q, что приводит к накоплению в клетке АФК, и, как следствие, гибели клетки вследствие окисления под действием АФК внутриклеточных субстратов. С другой стороны, в статье [85] высказана другая точка зрения заключающаяся в том, что хистатин-5 не приводит к повышению уровня АФК в клетках грибов, а фунгицидное действие этого пептида обусловлено вызванной им утечкой АТР из грибковых клеток.…”
Section: антимикробные пептиды с антигрибковой активностьюunclassified